Avaliação de métodos de extração de compostos bioativos das folhas de Pata de vaca (Bauhinia forficata subespécie pruinosa) - Palsikowski, Paula Alessandra (2020)
The cow´s paw (Bauhinia forficata) is a species of plant native to South America, largely used in folk medicine, mainly due to its hypoglycemic activity, that is related to the presence of flavonoids. This species is subdivided into two subspecies, of which B. forficata subsp. pruinosa, is practically unexplored scientifically. Thus, the aim of this study was to evaluate the extracts of cow´s paw leaves in terms of yield, chemistry composition, phenolic and flavonoid content, and antioxidant activity, obtained by various extraction methods: supercritical carbon dioxide and cosolvent, Soxhlet, maceration, pressurized liquids and ultrasound assisted extraction. The CO2 supercritical extractions were carried out at temperatures of 40, 50, and 60 oC, and pressures of 180, 200 and 220 bar, with a solvent volumetric flow rate of 2 mL.min-1 and 200 min of total extraction. The highest extraction yield obtained by supercritical extraction was 1.14% at 60 oC and 220 bar. The mathematical model developed by Sovová was applied to describe the kinetic extraction curves and it showed a good fit with the experimental data. Ethanol was used as cosolvent, providing up to 5.10% of yield in 120 min of extraction at 40 oC and 220 bar. The Soxhlet (360 min), maceration (7200 min), pressurized liquid (40, 50 and 60 oC; 100 bar and 40 min) and ultrasound assisted extractions (50 oC, 50% power, 15 mL.g-1 and 15 min) were conducted using ethanol, ethyl acetate and n-hexane as solvents. These extractions showed the affinity of the compounds for polar solvents, and the extracts obtained with ethanol showed the best results in relation to the yield, phenolic and flavonoid compounds, and antioxidant activity. Box–Behnken experimental design was applied to examine and optimize the effect of the extraction temperature (40, 50 and 60 oC), power (20, 50 and 80%), and solvent to leaves ratio (10, 15, and 20 mL.g-1) on the yield, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity by FRAP method of B. forficata leaves extracts. The experimental design generated second-order polynomial models, which accurately describe the experimental data, allowing predicting the optimal conditions for the investigated responses. Optimal extraction was achieved at 80% power, temperature of 41 °C, and solvent to leaves ratio of 20 mL.g-1. Under this condition, the experimental yield was 8.33±0.32%, total phenolic content was 59.47±0.71 mg GAE·gextract-1, the total flavonoid content was 62.30±3.38 mg QE·gextract-1 and the ferric reducing antioxidant power was 726.7±15.7 µmol Fe2+E·gextract-1, which were close to the predicted values, validating the models. In general, the phenolic, flavonoid content, and antioxidant activity of extracts obtained by unconventional methods with ethanol showed values close to and greater than those obtained by conventional methods. The major compounds found in B. forficata extracts were tocopherols, octacosanol, phytol, heneicosane and β-Sitosterol.